2013
DOI: 10.1103/physreva.88.022314
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a simple operator-quantum-error-correction scheme

Abstract: It is often assumed that the ancilla qubits required for encoding a qubit in quantum error correction (QEC) have to be in pure states, |00 . . . 0 for example. In this letter, we introduce an encoding scheme avoiding fully correlated errors, in which the ancillae may be in a uniformly mixed state. We demonstrate our scheme experimentally by making use of a three-qubit NMR quantum computer. Moreover, the encoded state has an interesting nature in terms of Quantum Discord, or purely quantum correlations between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Norm[Transpose[Q [3]]. X [7] Similarly, we can check the formula We can also check that for all n ≥ 3, P † n E(P n (σ ⊗ ρ)P † n )P n −σ ⊗ ρ = 0.…”
Section: Mathematicamentioning
confidence: 99%
See 1 more Smart Citation
“…Norm[Transpose[Q [3]]. X [7] Similarly, we can check the formula We can also check that for all n ≥ 3, P † n E(P n (σ ⊗ ρ)P † n )P n −σ ⊗ ρ = 0.…”
Section: Mathematicamentioning
confidence: 99%
“…So, for such a fully correlated channel, if one would like to protect 2k-qubit data states, only one additional qubit is needed, and using two additional qubits to protect the 2k-qubit data state seems to be a waste of resources. In [7], it was shown that one can use 2 arbitrary qubits to protect 1 data qubit in a fully correlated channel on 3-qubits.…”
Section: Introductionmentioning
confidence: 99%
“…The available code Q is used to correct a set of errors ⊂ E, and the dimension of Q is denoted nχ (1).…”
Section: Lemma 3 Let S Be a Certain Quantum Stabilizer Group In (21)mentioning
confidence: 99%
“…In quantum computation/communication systems, it is critical to maintain the coherence of a quantum system [1]. In practice, however, decoherence coming from the unwanted interaction between the system and the environment will collapse the state of the quantum communication/computation, thus making the information harder to correct [2].…”
Section: Introductionmentioning
confidence: 99%
“…The second QECC scheme is often called the "error-avoiding" coding due to this reason. Decoherence free subspace (DFS) and noiseless subsystem (NS) are two popular examples of the second kind [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%